KOMPONEN SINDROMA METABOLIK SEBAGAI FAKTOR RISIKO TERHADAP GEJALA DEPRESI - , Prahastya, dr. Agus Siswanto, Sp.PD-KPsi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The prevalence of metabolic syndrome is high enough around the world, its prevalence appears to be increasing due to the enhancement of obesity prevalence in parallel. According to the World Health Association (WHO), the metabolic syndrome is a new pandemic of the 21st century. It is estimated thatnumber of metabolic syndrome patients increased more than 50% at 20 years.6 Studies on the relationship of metabolic syndrome components and depressive symptoms result a significant association. Some studies showed that the incidence of depression will increase in patients with hypertension 15, diabetes mellitus type 27 and poor glycemic control in patients with diabetes mellitus type 2 with depression17,dyslipidemia13, and central obesity.16 Objective: To determine the role ofmetabolic syndrome components as a risk factorfor depressive symptoms. Methods :The study conducts with a case-control study design. Thesubjects compriseof 18 patients for sample and 18 patients for control.All the samplesare taken from patients treated at the department of internal medicine clinic of Dr. Sardjito hospital. The data is taken frominterviews, questionnaires and laboratory results. Continuous data arepresented in the form of mean Â± standard deviation (SD) and median (with the range of the minimum and maximum values), and categorical data are presented as a percentage. Differences demographic data , clinical characteristics and bivariate analysis using Chi-square or Fisher for categorical data and unpaired t-test for continuous data if the normal distribution or the Mann-Whitney test if the distribution is not normal. Distribution or the distribution of datais tested using the Shapiro-Wilk test because the sample size <50 .Multivariate analysis using the logistic regression analysis.